An improved collision - radiation model of the OH spectrum in the ultraviolet band. (September 2021) - Bai, Lu; Zhang, Dan-meng; Lv, Qiang; Zhang, Lin-lin; Wang, Yan-kun; Xu, Yue-yuan
Highlights: An improved collision radiation model is proposed to calculate the number density of OH(A) in the ultraviolet band of shock layer and plume. The influence of the collision between other heavy particles and OH in the plume on the number density is considered. The improved model can significantly enhance the applicability and accuracy of the excited state OH(A) spectrum in the plume. Abstract: In order to calculate the spectral radiation characteristics of OH( A 2 ∑) molecules more accurately, an improved collision-radiation (C-R) model is proposed to determine the excited states OH(A) number density. The six-components air model (CO, CO2, H2, H2 O, N2, and O2 ) instead of the two-components air model (N2 and O2 ) are used as other plume products in the excitation/de-excitation radiation reaction, and the rate of the four reactions are modified to improve the accuracy and applicability of the number density. Effects of temperature and other plume products on the number density of excited states are analyzed in the experiment, and the spectral radiation characteristics of OH(A) can be obtained by using this improved C-R model. Results of these calculations are then compared with other series of experimental data of exhaust plume and shock layer, the results show that both the original model and the improved model can be used to calculate the radiation characteristics in shock layer, however, due to the great error, the original model not apply to calculation of the OH(A) number density in exhaust plume, and the result of the improved model is in good agreement with the Atlas experimental data. As the vibrational-rotational level distribution number density has a close relationship with radiative spectral characteristics, a more focused OH(A) particle number density model will be more helpful to the hypersonic target detection and recognition.